FORMATION, DEVELOPMENT, ACHIEVEMENTS AND PROSPECTS OF WOMEN'S SPORTS IN NAVOI REGION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the formation, development, achievements and prospects of women's sports in the Navoi region. During the years of independence, the region covered various areas of women's sports — rhythmic gymnastics, judo, taekwondo, measures aimed at the development of chess and athletics, Public Policy and a system of incentives. In particular, the attitude and social attention to women's sports is reflected through the activities of sports girls who are the winners of the State prize named after Zulfiya. The development of mass sports is achieved through sports events held by enterprises and organizations in the region. The article also covers healthy lifestyles through women's sports, women's activism in society, and their impact on strengthening their social place.